2014
DOI: 10.1016/j.wear.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on rolling sliding wear behavior of wheel steel by laser dispersed treatment

Abstract: a b s t r a c tTo improve wear resistance of wheel steels under rolling-sliding wear conditions, a novel technique named laser dispersed treatment (LDT) was used by forming a regular scattered hardening pattern distributed on the surface of wheel disc, which can avoid soft zones induced by tempering effect or cracks in the overlapped region. The wear rate of LDT wheel disc was evaluated by twin-disc wear testing machine in comparison with the untreated disc. The microstructure of LDT wheel disc and untreated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…So, different friction enhancers are usually used to improve poor adhesion level for assuring adequate tractive or braking force [23]. It is clear in Fig.7 that the use of sand or alumina particles obviously increases the wear rate of rollers under water conditions compared to dry conditions.…”
Section: The Effect Of Friction Enhancersmentioning
confidence: 99%
See 1 more Smart Citation
“…So, different friction enhancers are usually used to improve poor adhesion level for assuring adequate tractive or braking force [23]. It is clear in Fig.7 that the use of sand or alumina particles obviously increases the wear rate of rollers under water conditions compared to dry conditions.…”
Section: The Effect Of Friction Enhancersmentioning
confidence: 99%
“…The high strength, fine lamellar pearlitic structure in rail steels is one of the most important factors for improving the wear resistance of material [22]. In addition, some researchers have explored the influence of laser surface treatment on the wear resistance of wheel and rail materials [23][24][25]. The results indicated that the laser treatment including laser dispersed quenching and laser cladding can significantly increase the hardness and wear resistance of wheel or rail material.…”
Section: Introductionmentioning
confidence: 99%
“…This method is similar to the target contact angle method [20]. Firstly, five hypotheses are introduced: (1) the wheel and rail are rigid, (2) the wheelset roll angle is ignored, (3) the shape of the rail is convex, (4) the shapes of the left and right wheels and rails are symmetrical, and (5) the contact between wheel and rail is represented by a contact point. In this method, the design of wheel tread is based on a specified rail profile.…”
Section: Single-objective Optimization Methodsmentioning
confidence: 99%
“…Most directly, slow wheel wear can improve wheel-track system performances, extend wheel re-profiling mileage, and reduce maintenance costs [1][2][3]. At present, the works on wheel wear reduction are mainly based on five aspects: (1) wheel-rail tribology [4][5][6][7][8], (2) wheel/rail profile optimization [9], (3) vehicle/track design [10][11][12][13], (4) active control of vehicle suspensions [14][15][16][17], and (5) track layout setting [18,19]. This article focuses on wheel profile optimization.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As a consequence, a new impulse in the study of wear and failure mechanisms and new materials has been under investigation in recent years. [4][5][6][7][8] A major method in the development of new wheel/ rail materials, especially the rail steel, is to improve the wear resistance and rolling contact fatigue (RCF) resistance through higher hardness. 9 Increasing hardness is relatively easy to achieve by adding alloying element (mainly manganese and vanadium) and applying heat treatment.…”
Section: Introductionmentioning
confidence: 99%